2005
DOI: 10.1081/clt-66079
|View full text |Cite
|
Sign up to set email alerts
|

Use of Amifostine, a Novel Cytoprotective, in α-Amanitin Poisoning

Abstract: No survival benefit was seen with cumulative doses between 250 and 500 mg/kg; however, higher doses may result in subsequent toxicity and decreased survival.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 29 publications
0
7
0
Order By: Relevance
“…The functions of IGFBP1 reported here provide a reasonable explanation for the lack of p53 mitochondrial accumulation or apoptosis induction reported previously for livers of mice following exposure to ␥-irradiation (Erster et al 2004). In contrast to such DNA damaging agents, ␣-amanitin has been shown to inhibit transcription and to elicit apoptosis in hepatocytes both in vitro and in vivo (Leist et al 1994;Hentze et al 2004;Wills et al 2005;Zhao et al 2006). This compound is the primary toxicological amatoxin in the "death cap" mushroom Amanita phalloides, and liver is one of the most sensitive organs to ␣-amanitin poisoning (Wills et al 2005;Zhao et al 2006).…”
Section: ␣-Amanitin Induces P53-mediated Mitochondrial Apoptosis In Lmentioning
confidence: 67%
See 1 more Smart Citation
“…The functions of IGFBP1 reported here provide a reasonable explanation for the lack of p53 mitochondrial accumulation or apoptosis induction reported previously for livers of mice following exposure to ␥-irradiation (Erster et al 2004). In contrast to such DNA damaging agents, ␣-amanitin has been shown to inhibit transcription and to elicit apoptosis in hepatocytes both in vitro and in vivo (Leist et al 1994;Hentze et al 2004;Wills et al 2005;Zhao et al 2006). This compound is the primary toxicological amatoxin in the "death cap" mushroom Amanita phalloides, and liver is one of the most sensitive organs to ␣-amanitin poisoning (Wills et al 2005;Zhao et al 2006).…”
Section: ␣-Amanitin Induces P53-mediated Mitochondrial Apoptosis In Lmentioning
confidence: 67%
“…In contrast to such DNA damaging agents, ␣-amanitin has been shown to inhibit transcription and to elicit apoptosis in hepatocytes both in vitro and in vivo (Leist et al 1994;Hentze et al 2004;Wills et al 2005;Zhao et al 2006). This compound is the primary toxicological amatoxin in the "death cap" mushroom Amanita phalloides, and liver is one of the most sensitive organs to ␣-amanitin poisoning (Wills et al 2005;Zhao et al 2006). However, little is known about the underlying molecular pathways involved.…”
Section: ␣-Amanitin Induces P53-mediated Mitochondrial Apoptosis In Lmentioning
confidence: 99%
“…They reported a LD 50 of 1000 mg/kg for a single injection or a cumulative dose of 4250 mg/kg divided into 10 injections over 11 days [21]. In a prior study, our lab similarly found evidence of cumulative toxicity and early deaths with a cumulative dose of 1600 mg/kg in mice poisoned with α-amanitin; however, control mice not poisoned with α-amanitin tolerated this dose [8]. We chose more moderate subcutaneous doses of amifostine because of its pharmacokinetic profile and our aim to provide sustained cytoprotection during the acute injury phase without causing inherent toxicity.…”
Section: Discussionmentioning
confidence: 68%
“…Amifostine is approved by the FDA for the prevention of toxicities associated with cisplatin and therapeutic radiation. Amifostine's unique cytoprotective effects have been extensively investigated by cancer treatment researchers, and only recently have its effects been studied as a potential antidote in a toxicologic model [7,8]. WR-1065 is an oxygen and DNA radical scavenger; it interferes with crosslinking of DNA, participates in DNA repair, and induces cellular hypoxia [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…Amifostine (Ethyol) a chemo protective agent is a pro drug that converts to its activated form (W-R 1065) by alkaline phosphatase. It has been approved by Food and Drug Administration (FDA) and its cytoprotective effects were examined during a lot of researches on cancer treatment [10]. W-R1065 acts as free radical scavenger and beside cytoprotective effects it can afford protection against toxic effects of ionizing radiation [11] and donates hydrogen ions for DNA repair [12].…”
Section: Introductionmentioning
confidence: 99%